Epizootic Ulcerative Syndrome (EUS) Fish Disease Chronology, Status and Major Outbreaks in the World - Kar Devashish (Sciendo, 2021)
Epizootic Ulcerative Syndrome (EUS) has been causing large-scale mortality among the freshwater fishes of the globe since the 1070s.